Basiswissen Echokardiografie : "Ars echocardiographica" – Schritt für Schritt zur korrekten Diagnose /: "Ars echocardiographica" – Schritt für Schritt zur korrekten Diagnose. (2017) - Hagendorff, Andreas; Stöbe, Stephan
No abstract available